2011
DOI: 10.1002/iub.544
|View full text |Cite
|
Sign up to set email alerts
|

Early endocrine and molecular changes in metabolic syndrome models

Abstract: SummaryThe twenty-first century arrived in the middle of a global epidemic of metabolic syndrome (MS) and type 2 diabetes mellitus (DM2). It is generally accepted that an excess of nutrients linked to a low physical activity triggers the problem. However, the molecular features that interact to develop the MS are not clear. In an effort to understand and control them, they have been extensively studied, but this goal has not been achieved yet. Nonhuman animal models have been used to explore diet and genetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 53 publications
3
33
0
8
Order By: Relevance
“…These findings are consistent with the notion that “excessive” activation of an already overworked beta cell under diabetic conditions during long-term treatment with incretin mimetics may lead to metabolic exhaustion of the beta cell (Araki et al, 2003; Larque et al, 2011) and, ultimately, compromised glucose homeostasis. This is conceptually important to consider prior to prescribing long-term multi-year continuous usage of GLP-1 analogs for the treatment of T2D.…”
Section: Resultssupporting
confidence: 90%
“…These findings are consistent with the notion that “excessive” activation of an already overworked beta cell under diabetic conditions during long-term treatment with incretin mimetics may lead to metabolic exhaustion of the beta cell (Araki et al, 2003; Larque et al, 2011) and, ultimately, compromised glucose homeostasis. This is conceptually important to consider prior to prescribing long-term multi-year continuous usage of GLP-1 analogs for the treatment of T2D.…”
Section: Resultssupporting
confidence: 90%
“…We used a model of MS in adult male Wistar rats as previously reported by our group (19). Briefly, MS was induced in 2-months-old rats by a hypercaloric diet over 8 weeks, which consisted of a 20% (w/v) sucrose solution as drinking water.…”
Section: Methodsmentioning
confidence: 99%
“…This effect could be partially prevented by inhibiting protease activity. To test if a similar process could be present in the whole animal, we used a rat model of MS (19, 20) that presents hyperinsulinemia. We observed that levels of circulating SIR were increased.…”
Section: Introductionmentioning
confidence: 99%
“…According to the definition of metabolic syndrome, all these changes indicate that the high-carbohydrates intake is sufficient to develop metabolic syndrome, as previously observed with a two months long treatment. 4 Since Reaven's metabolic syndrome description, 12 insulin resistance has been proposed as the key issue to understand its etiology. At present, it is well accepted that abdominal fat is frequently linked to insulin resistance and therefore obesity has been considered a risk factor for developing MS (for a review, see subpopulation 10.3 ± 0.6 was found compared with the others (Fig.…”
Section: Ms Rats Gain Weight and Fatmentioning
confidence: 99%
“…Hyperinsulinemia and insulin resistance are key issues to understanding MS. 3 We recently described that exposing Wistar young adult male rats to high sucrose in drinking water for two months induces MS. 4 Glucose-induced insulin secretion is a complex process of signal transduction in β cells, comprised by proximal events, which include glucose internalization through GLUT2 transporters and glucose metabolism that increase the ATP/ADP relationship, and by distal events, which include the activation of different ionic channels. Distal events start with the closure of ATP-sensitive Metabolic syndrome (MS) can be defined as a group of signs that increases the risk of developing type 2 diabetes mellitus (DM2).…”
Section: Introductionmentioning
confidence: 99%